An outline of solar photovoltaic systems impact on environment - Sarayu Vunnam; Muniyamuthu VanithaSri; RamaKoteswaraRao Alla (Bulletin of Electrical Engineering and Informatics, 2023)
The damaging environmental repercussions of energy production are greatly reduced when renewable energy sources are used. Solar photovoltaic (PV) energy is reliable and secure, and it also includes benefits like no noise, no pollution, easy maintenance, and no environmental harm. Solar PV technology has emerged as the renewable energy source with the greatest rate of expansion worldwide since fossil fuels are soon running out and have a negative influence on the environment. PV modules reduce carbon dioxide emissions, preserving the environment and preventing global warming. The solar cell efficiency is one of the key elements in developing this PV technology. To increase solar cell efficiency for commercial use, the type of material used in production is essential. After serving its purpose, a PV module can be recycled, and environmentally appropriate disposal won't have much of an effect on the environment. In this article, the impact of solar PV systems and their most recent advancements for environmental preservation are discussed.